Inclusive Refugee-Hosting in Uganda Improves Local Development and Prevents Public Backlash - Zhou, Yang-Yang; Grossman, Guy; Ge, Shuning (World Bank, Washington, DC, 2022)
Large arrivals Aof refugees raise concerns about potential tensions with host communities, particularly if refugees are viewed as an out-group competing for limited material resources and crowding out public services. To address this concern, calls have increased to allocate humanitarian aid in ways that (also) benefit host communities. This study empirically tests whether the presence of refugees in Uganda (one of the largest refugee-hosting countries) has improved public service delivery, and consequently, dampened potential social conflict. The data combines geospatial information on refugee settlements with unique longitudinal data on primary and secondary schools, road density, health clinics, and health utilization. This study reports two key findings. First, particularly after the 2014 arrival of over 1 million South Sudanese refugees, host communities with greater levels of refugee presence experienced substantial improvements in local development. Second, using public opinion data, we find no evidence that refugee presence is associated with more negative (or positive) attitudes towards migrants or migration policy.